تقييم أداء تقنيات إدارة الطّاقة في الأنظمة المضمنة المتنقلة باعتبار آليات النفاذ للوسط - دندة رضوان; صبيح محمد; حيدر هبة (Latakia University Journal -Engineering Sciences Series, 2017)
أصبحت تقنية التشبيك اللاسلكية (Wi-Fi) معياراً فعلياً للوصول اللاسلكي إلى الانترنت، ومع تزايد توافرية نقاط وصول لتلك الشبكات اللاسلكية نتيجةَ ما تقدّمهُ من معدّلات بيانات مرتفعة، تكاليف تجوال منخفضة، وتغطية جيدة داخل المباني، أصبح هنالك اتجاه قوي لإدراج النظّام الفرعي المضمّن Wi-Fiفي كل أنواع الأجهزة سواء الحاسوبية منها أو المضمّنة. كان لزاماً على الهواتف الذّكية مع تبنيها لتقنيةWi-Fi تلبية مطلبين هما: -1 دعم جودة الخدمة من أجل إعطاء تفضيل لتطبيقات الزّمن الحقيقي. 2- تضمين وظائف توفير الطّاقة لتحقيق زمن تشغيل يلبي توقعات المُستخدمين. قدّم هذا البحث تقنيةً جديدة لإدارة الطّاقةP-PSM ، وهي عبارة عن دمجٍ لتقنية إدارة الطّاقة القياسية stdPSM، مع آليةِ نفاذٍ للوسط تعتمد على نافذةِ المنافسة للتزويد بجودة الخدمة، حيثُ جرى تقييم أدائها مقابلَ مجموعةٍ من تقنيات إدارة الطّاقة في ظل تغيير عدد العقد الشبكية، بغيةَ توضيحِ اختلافات الأداء من ناحيتي توفير الطّاقة وجودة الخدمة. Wireless LAN technology has become the actual standard for wireless Internet access, with increasing availability of access points for those wireless networks as a result of what they offer of high data rates, low roaming costs, and good in-building coverage. This led to a strong trend to the inclusion of Wi-Fi embedded sub-system in all kinds of devices included computing side, and embedded side.The smartphones with the adoption of Wi-Fi technology had to meet two requirements: 1- quality of service support for prioritizing real-time applications. 2- inclusion of power saving functionality to achieve an operating time meets the expectations of users. This paper presents a new power management technique P-PSM, it is a combination of medium access mechanism depends on Contention Window to provide the quality of service, with standard power management technology stdPSM. In addition to evaluate its performance against a set of power management techniques under changing the number of network nodes in order to clarify the expected quantity differences in terms of both quality of service and power saving.